Motion Control Of Biped Robot - Lim, Chot Hun (2006)
In this project, a 17-joint high precision biped robot (with 3 -joints on each arm, 5-joints on each leg, and one joint for its head), called KHR-1, is chosen as the platform for studying biped's motion control.